Tissue engineering small diameter blood vessels - fabrication of porous scaffold. - Chng, Hui Peng. (2010)
The development of tissue engineered small diameter blood vessels as biological grafts are in growing demand for patients requiring cardiovascular surgery. However, the reconstruction of a functional vascular media with cell culture and suitable mechanical properties has yet to be established. The objective of this study is to fabricate porous scaffold with high porosity and good degree of pore interconnectivity. The methodology used to synthesize the scaffold involves the combination of emulsification and ultraviolet irradiation. Experimental conditions were varied to determine the effects of changing the water-polymer (aqueous calcium chloride-PCLLGA) ratios. In addition, PEGDA was also added as a crosslinker to enhance the mechanical properties of the scaffold. Polymer scaffolds of about 40%~55% in porosity and 80~300 μm in pore sizes were successfully synthesized. The findings of this project may be used for further study in the effects of co-culture of endothelial cells and smooth muscle cells.